A carbon / carbon composite material and preparation method thereof

Through multi-layer weaving and plasma treatment, a strongly interacting interface layer is formed, and a variety of modified components and antioxidants are added to the carbon matrix to optimize the interface microstructure, solving the problems of insufficient interface binding force and weak oxidation resistance of existing carbon/carbon composite materials, and achieving high strength, stability and high temperature resistance of the material.

CN119390468BActive Publication Date: 2025-03-25YOUCAITEC MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510016386.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-25
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The interface binding force of existing carbon/carbon composite materials is insufficient, resulting in interface separation under complex working conditions and weak oxidation resistance.

Method used

A variety of carbon fiber types such as polyacrylonitrile-based carbon fiber, asphalt-based carbon fiber, nanosilica grafted carbon fiber, etc. are adopted to form a strongly interacting interface layer through multi-layer braiding and plasma treatment, and bioasphalt, nanographene-modified phenolic resin, zirconium boronide nanoparticles, cerium oxide nanoparticles, yttria nanoparticles and natural plant extract antioxidants are added to the carbon matrix to optimize the interface microstructure through thermal gradient chemical vapor deposition and high-temperature heat treatment.

Benefits of technology

It significantly enhances the interface bonding and oxidation resistance of carbon/carbon composite materials, ensures the structural integrity and mechanical properties of the material under a variety of complex stresses, and broadens its application range in the field of high-temperature oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390468B_ABST
    Figure CN119390468B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of material preparation, and is intended to solve the problem that the interface separation and the weak oxidation resistance of the existing carbon / carbon composite material due to insufficient interface bonding force lead to the occurrence of interface separation under complex working conditions. For this purpose, the present invention provides a kind of carbon / carbon composite material and its preparation method, and the carbon / carbon composite material is measured by mass percentage including: polyacrylonitrile-based carbon fiber 40%-55%, asphalt-based carbon fiber 10%-25%, nano-silicon dioxide grafted carbon fiber 8%-20%, bio-asphalt 8%-20%, nano-graphene modified phenolic resin 8%-15%, silicon carbide whisker 3%-6%, zirconium boride nanoparticles 2%-4%, graphitized carbon fiber 2%-4% and natural plant extract antioxidant 1%-3%. The carbon / carbon composite material of the present invention can provide stable interface bonding force and significant oxidation resistance, so as to ensure the structural integrity and mechanical property stability of the material when subjected to multiple complex stresses such as tension, compression, bending, shearing, and widen its application range in the field of high temperature oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a carbon / carbon composite material and a preparation method thereof. Background Art

[0002] With the rapid development of modern science and technology, the field of materials science is constantly facing new challenges and opportunities. Among many high-performance materials, carbon / carbon composites have attracted much attention due to their unique performance advantages.

[0003] The performance requirements for materials in many industrial fields such as aerospace, automobile manufacturing, and energy are becoming increasingly stringent. For example, the aerospace field requires materials with high strength, low density, high temperature resistance, and excellent antioxidant properties to meet the structural load-bearing and thermal protection requirements of aircraft in extreme environments; the automobile manufacturing industry pursues materials that can both reduce the weight of the vehicle body to improve fuel efficiency and maintain good mechanical and thermal stability in high-temperature components such as engines; some high-temperature equipment in the energy field, such as nuclear reactors and solar thermal utilization devices, also urgently need materials that can work stably for a long time under harsh conditions such as high temperature and radiation. Traditional single materials or conventional composite materials can no longer fully meet these complex and diverse performance requirements, so the development of new high-performance composite materials has become an important direction for material research.

[0004] Carbon materials themselves have some unique properties. For example, carbon fibers have high strength and modulus, and the carbon matrix can provide certain stability and support. However, pure carbon materials still have limitations in certain performance aspects. For example, the interface bonding between ordinary carbon fibers and the carbon matrix is ​​not ideal, and interface separation is prone to occur during stress or heat treatment, thus affecting the overall mechanical and thermal properties of the material. At the same time, in a high-temperature oxidizing environment, carbon materials are prone to oxidation reactions, resulting in a decrease in material performance or even failure.

[0005] In view of this, the art needs a carbon / carbon composite material and a preparation method thereof to solve the above problems. Summary of the invention

[0006] In order to solve the above technical problems, that is, to solve the problem that the interface bonding force of existing carbon / carbon composite materials is insufficient, resulting in interface separation under complex working conditions and weak antioxidant performance.

[0007] In a first aspect, the present invention provides a carbon / carbon composite material, which comprises, by weight percentage, 40%-55% polyacrylonitrile-based carbon fiber, 10%-25% asphalt-based carbon fiber, 8%-20% nano-silicon dioxide grafted carbon fiber, 8%-20% bio-asphalt, 8%-15% nano-graphene modified phenolic resin, 3%-6% silicon carbide whiskers, 2%-4% zirconium boride nanoparticles, 2%-4% graphitized carbon fiber and 1%-3% natural plant extract antioxidant.

[0008] In certain preferred embodiments, the carbon / carbon composite material comprises, by weight percentage, 42%-47% polyacrylonitrile-based carbon fiber, 10%-16% asphalt-based carbon fiber, 10%-16% nano-silica grafted carbon fiber, 10% bio-asphalt, 10% nano-graphene modified phenolic resin, 4% silicon carbide whiskers, 3% boride nanoparticles, 3% graphitized carbon fiber and 2% natural plant extract antioxidant.

[0009] In certain preferred embodiments, the carbon / carbon composite material further comprises 3%-6% rare earth oxide.

[0010] In certain preferred embodiments, the rare earth oxides include 2%-4% cerium oxide and 1%-2% yttrium oxide.

[0011] The carbon / carbon composite material of the present invention has the following beneficial effects:

[0012] In the carbon / carbon composite material of the present invention, the nano-silica on the surface of the nano-silica grafted carbon fiber forms a strongly interactive interface layer with the carbon matrix through chemical bonding and physical adsorption. This interface layer is like an "anchor agent", which effectively enhances the connection strength between the carbon fiber and the carbon matrix, and greatly reduces the possibility of interface separation under complex stress conditions. At the same time, the bio-asphalt and nano-graphene modified phenolic resin can fully infiltrate and wrap the carbon fiber in the process of forming the carbon matrix, further fill the microscopic gaps between the fiber and the matrix, and make the interface bonding tighter. In addition, different types of carbon fibers such as asphalt-based carbon fibers, polyacrylonitrile-based carbon fibers and graphitized carbon fibers are interwoven to form a stable fiber network structure. When interacting with the carbon matrix, the interface contact area and contact points are increased, and the overall interface bonding force is strengthened from multiple dimensions, thereby ensuring the structural integrity and mechanical performance stability of the material when subjected to various complex stresses such as tension, compression, bending and shearing; in addition, zirconium boride nanoparticles can preferentially bond to the carbon fiber under high temperature conditions. It reacts with oxygen to form a dense and stable zirconium oxide protective film on the surface of the material, which effectively prevents oxygen from diffusing into the interior of the material. Cerium oxide nanoparticles and yttrium oxide nanoparticles use their unique redox properties to build a dynamic antioxidant defense system on the surface of the material, which can timely capture and neutralize the free radicals generated by the material during high-temperature oxidation and inhibit the oxidation chain reaction. Natural plant extract antioxidants serve as auxiliary antioxidant ingredients to further enhance the antioxidant capacity of the material in different temperature ranges. These antioxidant components work synergistically with the carbon matrix and carbon fibers. On the one hand, the carbon matrix provides a stable attachment basis for the antioxidant components, allowing them to be evenly distributed and continuously exert an antioxidant effect. On the other hand, carbon fibers can disperse oxidation stress to a certain extent and reduce local oxidation damage. There is also a certain mutual protection mechanism between them and the antioxidant components, which together improve the antioxidant performance of the material in harsh environments such as high temperature and oxidation, significantly extend the service life of the material, and broaden its application range in the field of high-temperature antioxidant.

[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned carbon / carbon composite material, the preparation method comprising:

[0014] S1: polyacrylonitrile-based carbon fiber, asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber are multi-layered woven according to an inside-outside gradient structure to obtain a preform;

[0015] S2: placing the braided preform in a plasma treatment device for plasma treatment;

[0016] S3: preparing a precursor solution containing bio-asphalt and nano-graphene modified phenolic resin, adding silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants to the precursor solution, and then sequentially or simultaneously subjecting the mixed solution to ultrasonic treatment and stirring treatment;

[0017] S4: placing the preform into an impregnation container, injecting the mixed solution and sealing the container, and filling the impregnation container with supercritical carbon dioxide;

[0018] S5: placing the impregnated preform into a microwave curing device for curing;

[0019] S6: placing the preform in a chemical vapor deposition reaction chamber to perform thermal gradient chemical vapor deposition;

[0020] S7: placing the preform after chemical vapor deposition in a pressure impregnation device, injecting the mixed solution into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix;

[0021] S8: placing the composite material that has undergone the infiltration treatment into a high-temperature heat treatment furnace for high-temperature heat treatment.

[0022] In certain preferred embodiments, in step S2, the plasma power of the plasma treatment equipment is 100-300 watts, the treatment time is 10-30 minutes, and the gas is a mixture of oxygen and argon with an oxygen content of 10%-30%.

[0023] In certain preferred embodiments, in step S3, the ultrasonic treatment is performed for 30-60 minutes, and the stirring treatment is performed at 200-300° C. and 1000-2000 rpm for 60-120 minutes.

[0024] In certain preferred embodiments, in step S4, the supercritical carbon dioxide is charged to a set pressure of 8-15 MPa, a temperature of 40-60° C., and an immersion treatment time of 2-4 hours;

[0025] In step S5, the curing treatment is performed at a power of 500-1000 watts, a time of 10-20 minutes, and a temperature of 150-200°C.

[0026] In certain preferred embodiments, in step S6, during the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 50-100 ml / min, the hydrogen flow rate is 200-400 ml / min, the center temperature of the thermal gradient is 800-1000° C., the edge temperature is 600-800° C., and the deposition time is 2-5 hours;

[0027] In step S7, the pressure of the pressure impregnation equipment is 2-5 MPa, the temperature is 80-120°C, and the infiltration treatment time is 1-3 hours.

[0028] In some preferred embodiments, step S8 specifically includes:

[0029] S81: placing the composite material into a high temperature heat treatment furnace, introducing argon gas, heating to 1500-1800° C. at a heating rate of 3-8° C. / min, and keeping the temperature for 1.5-3.5 hours;

[0030] S82: Continue to increase the temperature to 2000-2500° C. at a heating rate of 2-4° C. / min, and keep the temperature for 2.5-4.5 hours.

[0031] The preparation method of the carbon / carbon composite material of the present invention has the following beneficial effects:

[0032] In the preparation method of the carbon / carbon composite material of the present invention, a multi-layered woven carbon fiber preform is firstly woven according to the internal and external gradient structure, which lays a structural foundation for the subsequent enhancement of the interface bonding force. The rational layout of different types of carbon fibers enables each fiber to fully contact with the matrix precursor and form a multi-layered bonding interface during the subsequent processing. The plasma treatment is used to activate the surface of the woven preform, and active sites are introduced on the surface of the carbon fiber, which greatly improves the reaction activity and affinity of the carbon fiber and the subsequent carbon matrix precursor. The configured precursor solution is added with a variety of components that are conducive to interface bonding, such as bio-asphalt and nano-graphene modified phenol. Formaldehyde resin, etc. In the subsequent impregnation and penetration, these components can fully fill the pores between carbon fibers and closely combine with the surface of carbon fibers under the action of pressure (supercritical carbon dioxide pressure and pressure impregnation pressure) and temperature (impregnation and penetration temperature) to form a strong interface connection. In the process of microwave curing to convert the precursor into a carbon matrix, the uniform heating characteristics of microwaves can reduce the internal stress of the interface caused by uneven curing and further stabilize the interface structure. In the process of thermal gradient chemical vapor deposition depositing carbon on the surface and pores of the preform, the deposited carbon can fuse with the carbon fibers and the previously impregnated and infiltrated matrix components. The interface microstructure is optimized, and the interface bonding strength is synergistically improved from multiple links. In addition, the zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants added in the preparation method are uniformly dispersed in the solution and can be evenly distributed in the preform and the formed carbon matrix through supercritical carbon dioxide assisted impregnation, microwave curing and pressure impregnation. During high-temperature heat treatment, these antioxidant components play a role in different temperature ranges. The zirconium boride nanoparticles are the first to form a protective film at high temperature, and the cerium oxide and yttrium oxide nanoparticles participate in the regulation of the antioxidant reaction during the entire high-temperature process. The natural plant extract antioxidant The antioxidant agent assists in enhancing the antioxidant effect, and the cooperation between each step ensures that a good synergistic system is formed between the antioxidant components and the carbon matrix and carbon fiber. The plasma treatment not only enhances the interfacial bonding force, but also may improve the antioxidant properties of the carbon fiber surface to a certain extent, providing better conditions for the subsequent attachment and action of the antioxidant components. The carbon structure formed by thermal gradient chemical vapor deposition can provide certain physical support and diffusion channels for the antioxidant components, which is beneficial to the uniform formation and stable existence of the antioxidant protective film, thereby comprehensively improving the antioxidant properties of the material and enabling the material to operate stably for a long time in a high-temperature oxidizing environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The features and advantages of the present invention will be more clearly understood by referring to the accompanying drawings, which are schematic and should not be construed as limiting the present invention in any way. In the accompanying drawings:

[0034] Figure 1 The present invention is a flow chart of a method for preparing a carbon / carbon composite material. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0036] Based on the problem pointed out in the background technology that the interface bonding strength of existing carbon / carbon composite materials is insufficient, resulting in interface separation under complex working conditions and weak antioxidant performance, the present invention provides a carbon / carbon composite material and a preparation method thereof, aiming to enable the carbon / carbon composite material to provide stable interface bonding strength and significant antioxidant properties, thereby ensuring the structural integrity and mechanical property stability of the material when subjected to various complex stresses such as tension, compression, bending and shear, and broadening its application scope in the field of high-temperature antioxidant.

[0037] The carbon / carbon composite material of the present invention comprises, by weight percentage, 40%-55% of polyacrylonitrile-based carbon fiber, 10%-25% of asphalt-based carbon fiber, 8%-20% of nano-silicon dioxide grafted carbon fiber, 8%-20% of bio-asphalt, 8%-15% of nano-graphene modified phenolic resin, 3%-6% of silicon carbide whisker, 2%-4% of boronized zirconium nanoparticles, 2%-4% of graphitized carbon fiber, and 1%-3% of natural plant extract antioxidant. More preferably, the carbon / carbon composite material comprises, by weight percentage, 42%-47% of polyacrylonitrile-based carbon fiber, 10%-16% of asphalt-based carbon fiber, 10%-16% of nano-silicon dioxide grafted carbon fiber, 10% of bio-asphalt, 10% of nano-graphene modified phenolic resin, 4% of silicon carbide whisker, 3% of boronized zirconium nanoparticles, 3% of graphitized carbon fiber, and 2% of natural plant extract antioxidant.

[0038] In the above, the polyacrylonitrile-based carbon fiber preferably adopts high-strength and high-modulus polyacrylonitrile-based carbon fiber, and the grade is preferably T1000 grade. The asphalt-based carbon fiber preferably adopts high thermal conductivity asphalt-based carbon fiber. The natural plant extract antioxidant can use plant extracts containing flavonoids (such as ginkgo leaf extract) as antioxidants. Flavonoids have multiple phenolic hydroxyl groups and can provide hydrogen atoms to combine with free radicals, thereby terminating the free radical chain reaction. In the two-stage high-temperature heat treatment process, when the temperature rises, the ginkgo leaf extract can form an antioxidant protective layer on the surface and inside of the material to prevent excessive oxidation of the carbon / carbon composite material in a high temperature environment and protect the structure and performance of the material. Of course, the natural plant extract antioxidant can also use rosemary extract antioxidants, etc.

[0039] In a preferred embodiment, the carbon / carbon composite material of the present invention further comprises 3%-6% of rare earth oxides, and more preferably, the rare earth oxides comprise 2%-4% of cerium oxide and 1%-2% of yttrium oxide. In the carbon / carbon composite material, cerium oxide and yttrium oxide as rare earth oxides have some common excellent properties. They can react with oxygen at high temperatures to form a dense protective film on the surface of the material. Specifically, cerium oxide can be formed by Ce 4+ / Ce 3+ The protective film can prevent oxygen from further diffusing into the material, thereby effectively improving the material's antioxidant properties. At the same time, rare earth oxides can also refine the grains. During the material preparation process, especially during the high-temperature heat treatment stage, cerium oxide and yttrium oxide can inhibit the growth of grains, improve the material's microstructure, and make the material's performance more stable. During the high-temperature oxidation process, the refined grain structure can reduce oxidation channels, reduce the oxidation rate, and further improve the material's antioxidant properties.

[0040] like Figure 1 As shown, the preparation method of the carbon / carbon composite material of the present invention comprises:

[0041] S1: Polyacrylonitrile-based carbon fiber, asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber are woven in multiple layers according to an inside-outside gradient structure to obtain a preform.

[0042] In a preferred embodiment, the multi-layer weaving steps are performed sequentially by inner layer weaving, middle layer weaving and outer layer weaving.

[0043] Specifically, the inner layer is woven first: the length of the T1000-level high-strength and high-modulus polyacrylonitrile-based carbon fiber is controlled at 3-6 mm, the selected carbon fiber is pre-stretched, and the pre-stretching stress is set to 5%-10% of its breaking strength. The pre-stretching state is maintained for 10-15 minutes to eliminate the residual stress inside the fiber and improve its stability and consistency of mechanical properties during the weaving process. The pre-treated high-strength and high-modulus polyacrylonitrile-based carbon fiber is transported to the weaving area through an automated feeding device, and the mechanical weaving device is guided by a fiber guide device at an alternating weaving angle of 0° / 90° and a fiber density of about 100-150 strands / cm2. The weaving speed is controlled at 10-20 mm / s. During the weaving process, a constant tension is applied to each fiber through a tension sensor. The tension value is set to 5-10 grams, and the error range is controlled within the weaving angle error ±1° and the fiber density error ±5 fibers / square centimeter. Then the middle layer is woven: when the inner layer weaving reaches a predetermined thickness (preferably 30%-40% of the total thickness of the preform), high thermal conductivity asphalt-based carbon fibers, nano-silicon dioxide grafted carbon fibers and graphitized carbon fibers are gradually introduced for middle layer weaving. The length of the high thermal conductivity asphalt-based carbon fibers is 2-5 mm, the length of the nano-silicon dioxide grafted carbon fibers is 1-4 mm, and the length of the graphitized carbon fibers is 0.5-2 mm, first, according to the ratio of high-strength and high-modulus polyacrylonitrile-based carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano-silica grafted carbon fiber: graphitized carbon fiber = 7:1:1:1, the four carbon fibers are evenly mixed in an automated fiber mixing device, a stirring device is provided in the mixing device, the stirring speed is 50-100 rpm, the stirring time is 10-15 minutes, and ultrasonic vibration is used at the same time, the ultrasonic power is 200-300 watts, and the ultrasonic time is 5-10 minutes to ensure that the fibers are fully mixed and no entanglement occurs, the mixed fibers are transferred to the middle layer weaving mold through an automated conveying system, and weaving is performed according to the requirement of adjusting the weaving angle to ±30° / ±60°. The middle layer weaving mold inherits part of the structure and function of the inner layer weaving mold, and the fiber guide device is reset, and the fiber density is gradually reduced to 80-120 roots / cm2. During the weaving process, the weaving speed is 8-15 mm / s; finally, the outer layer is woven: when the middle layer After the weaving reaches the predetermined thickness (preferably 50%-60% of the total thickness of the preform), the ratio of the four carbon fibers is further adjusted to make high-strength and high-modulus polyacrylonitrile-based carbon fibers: high thermal conductivity asphalt-based carbon fibers: nano-silica grafted carbon fibers: graphitized carbon fibers = 5:2:2:1. The fibers are remixed in an automated fiber mixing container according to the new ratio. The stirring and ultrasonic treatment parameters are the same as those for the middle layer mixing to ensure uniform fiber mixing. The mixed fibers are sent to the outer layer weaving mold through an automated delivery pipeline and weaved at a weaving angle of ±30° / ±60°. The weaving speed is controlled at 6-12 mm / s. After weaving, the preform is post-processed as a whole, including removing surface impurities and loose fibers through an automated cleaning device, and then performing automated pre-compaction treatment. The pre-compaction strength is 0.5-1 MPa and the pre-compaction time is 10-15 minutes to improve the overall stability and structural integrity of the preform, and finally form a preform structure with gradual mechanical and thermal properties. .

[0044] S2: placing the braided preform in a plasma treatment device for plasma treatment.

[0045] Preferably, in the above step S2, the plasma power of the plasma treatment equipment is 100-300 watts, the treatment time is 10-30 minutes, the gas is a mixture of oxygen and argon, the oxygen content is 10%-30%, and active particles are used to etch impurities and weak bonding layers on the surface of the carbon fiber. Argon ion impact produces active sites to enhance the bonding force with the carbon matrix precursor.

[0046] S3: preparing a precursor solution containing bio-asphalt and nano-graphene modified phenolic resin, adding silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants to the precursor solution, and then performing ultrasonic treatment and stirring treatment on the mixed solution sequentially or simultaneously.

[0047] Preferably, in the above step S3, the ultrasonic treatment time is 30-60 minutes, and the stirring treatment is carried out at 200-300° C. and 1000-2000 rpm for 60-120 minutes to ensure that the additives are evenly dispersed.

[0048] S4: placing the preform into an impregnation container, injecting the mixed solution and sealing the container, and filling the impregnation container with supercritical carbon dioxide.

[0049] Preferably, in the above step S4, the set pressure of supercritical carbon dioxide is 8-15 MPa, the temperature is 40-60° C., the immersion treatment time is 2-4 hours, and then the pressure is slowly released to allow excess solution to flow out.

[0050] S5: placing the impregnated preform into a microwave curing device for curing.

[0051] Preferably, in the above step S5, the curing treatment power is 500-1000 watts, the time is 10-20 minutes, the temperature is 150-200°C, and the phenolic resin is cured by microwave heating to form a preliminary carbon matrix. During curing, volatiles can be removed by vacuum to improve density.

[0052] S6: placing the preform in a chemical vapor deposition reaction chamber to perform thermal gradient chemical vapor deposition.

[0053] Preferably, in the above step S6, during the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 50-100 ml / min, the hydrogen flow rate is 200-400 ml / min, the center temperature of the thermal gradient is 800-1000°C, the edge temperature is 600-800°C, and the deposition time is 2-5 hours. At the same time, the precursors of cerium oxide and yttrium oxide are dissolved in a solvent, mixed with the gas source in an atomized form and introduced into the reaction chamber, so that cerium oxide and yttrium oxide are deposited on the surface and pores of the preform together with carbon.

[0054] S7: placing the preform after chemical vapor deposition in a pressure impregnation device, injecting the mixed solution into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix.

[0055] Preferably, in the above step S7, the pressure of the pressure impregnation equipment is 2-5 MPa, the temperature is 80-120° C., and the infiltration treatment time is 1-3 hours, so that the liquid precursor and the chemical vapor deposited carbon are combined with each other to densify the carbon matrix.

[0056] S8: placing the composite material that has undergone the infiltration treatment into a high-temperature heat treatment furnace for high-temperature heat treatment.

[0057] Preferably, the above step S8 specifically includes:

[0058] S81: Place the composite material into a high-temperature heat treatment furnace, introduce argon gas, heat to 1500-1800°C at a heating rate of 3-8°C / min, and keep warm for 1.5-3.5 hours. During this process, the carbon atoms in the carbon matrix are rearranged, the structure is regularized, part of the amorphous carbon is converted into graphite carbon, and cerium oxide and yttrium oxide begin to play an antioxidant role to protect the material structure.

[0059] S82: Continue to heat up to 2000-2500℃ at a heating rate of 2-4℃ / min, and keep warm for 2.5-4.5 hours. At this time, the graphitization degree of the carbon matrix is ​​deepened, the crystal structure is perfected, cerium oxide and yttrium oxide are further integrated into the material structure to form a stable antioxidant layer, thereby improving the high-temperature antioxidant and comprehensive performance of the material. After the treatment is completed, cool to room temperature with the furnace to obtain the final carbon / carbon composite material.

[0060] The technical solution of the present invention is further described below through a plurality of embodiments and comparative examples.

[0061] Embodiment 1

[0062] The carbon / carbon composite materials measured by mass percentage include: the carbon / carbon composite materials measured by mass percentage include: polyacrylonitrile-based carbon fiber 45%, asphalt-based carbon fiber 10%, nano-silica grafted carbon fiber 10%, bio-asphalt 10%, nano-graphene modified phenolic resin 10%, silicon carbide whiskers 4%, zirconium boride nanoparticles 3%, graphitized carbon fiber 3%, ginkgo leaf extract antioxidant 2%, cerium oxide 2% and yttrium oxide 1%.

[0063] The method for preparing the carbon / carbon composite material comprises:

[0064] The length of T1000-level high-strength and high-modulus polyacrylonitrile-based carbon fiber is controlled at 3-6 mm, and the selected carbon fiber is pre-stretched. The pre-stretching stress is set to 10% of its breaking strength. The pre-stretching state is maintained for 15 minutes, and the pre-treated high-strength and high-modulus polyacrylonitrile-based carbon fiber is transported to the weaving area through an automatic feeding device. According to the alternating weaving angle of 0° / 90° and the fiber density of about 150 strands / square centimeter, it is woven by a mechanical weaving device under the guidance of a fiber guide device. The weaving speed is controlled at 20 mm / second. During the weaving process, each fiber is tensioned by a tension sensor. Apply constant tension, the tension value is set to 10 grams, the error range is controlled within the weaving angle error of ±1°, the fiber density error is ±5 roots / square centimeter; then carry out the middle layer weaving: when the inner layer weaving reaches 35% of the total thickness of the preform, begin to gradually introduce high thermal conductivity asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber for middle layer weaving, the high thermal conductivity asphalt-based carbon fiber length is 2-5 mm, the nano-silica grafted carbon fiber length is 1-4 mm, the graphitized carbon fiber length is 0.5-2 mm, first, according to the high strength and high modulus polyacrylonitrile-based carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano Silica grafted carbon fiber: graphitized carbon fiber = 7:1:1:1 ratio. The four carbon fibers are mixed and stirred evenly in an automated fiber mixing device at a stirring speed of 100 rpm for 15 minutes. Ultrasonic vibration is also used at a power of 300 watts for 10 minutes. The weaving is carried out according to the requirements of adjusting the weaving angle to ±30° / ±60°. The fiber density gradually decreases to 120 fibers / cm2. During the weaving process, the weaving speed is 15 mm / s. Finally, the outer layer is woven: when the middle layer weaving reaches 60% of the total thickness of the preform, the high-strength and high-modulus polyacrylonitrile is made. Base carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano-silica grafted carbon fiber: graphitized carbon fiber = 5:2:2:1. The fibers are remixed in a new ratio in an automated fiber mixing container. The stirring and ultrasonic treatment parameters are the same as those for the middle layer mixing. The mixed fibers are sent to the outer layer weaving mold through an automated delivery pipeline and weaved at a weaving angle of ±30° / ±60°. The weaving speed is controlled at 12 mm / s. After weaving, the surface impurities and loose fibers are removed by an automated cleaning device, and then automated pre-compaction treatment is carried out. The pre-compaction strength is 1 MPa and the pre-compaction time is 15 minutes.

[0065] The braided preform is placed in a plasma treatment device for plasma treatment. The plasma power of the plasma treatment device is 100 watts, the treatment time is 10 minutes, and the gas is a mixture of oxygen and argon with an oxygen content of 10%.

[0066] A precursor solution containing bio-asphalt and nano-graphene modified phenolic resin is prepared, silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants are added to the precursor solution, and then the mixed solution is subjected to ultrasonic treatment and stirring treatment in sequence, the ultrasonic treatment time is 30 minutes, and the stirring treatment is carried out at 200°C and 1000 rpm for 60 minutes.

[0067] The preform is placed in an impregnation container, the mixed solution is injected and then sealed, supercritical carbon dioxide is charged into the impregnation container, the pressure is set to 8 MPa, the temperature is 40° C., and the impregnation treatment time is 2 hours.

[0068] The impregnated preform was placed in a microwave curing device for curing at a power of 500 watts, a time of 10 minutes, and a temperature of 150°C.

[0069] The preform is placed in a chemical vapor deposition reaction chamber for thermal gradient chemical vapor deposition. During the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 50 ml / min, the hydrogen flow rate is 200 ml / min, the center temperature of the thermal gradient is 800°C, the edge temperature is 600°C, and the deposition time is 2 hours.

[0070] The preform after chemical vapor deposition is placed in a pressure impregnation device, and the mixed solution is injected into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix. The pressure of the pressure impregnation device is 2 MPa, the temperature is 80°C, and the infiltration treatment time is 1 hour.

[0071] The infiltration-treated composite material was placed in a high-temperature heat treatment furnace, argon gas was introduced, and the material was heated to 1500°C at a heating rate of 3°C / min, kept warm for 1.5 hours, and then heated to 2000°C at a heating rate of 2°C / min, kept warm for 2.5 hours. After the treatment, the material was cooled to room temperature with the furnace to obtain the final carbon / carbon composite material.

[0072] Embodiment 2

[0073] The carbon / carbon composite materials measured by mass percentage include: the carbon / carbon composite materials measured by mass percentage include: polyacrylonitrile-based carbon fiber 45%, asphalt-based carbon fiber 10%, nano-silica grafted carbon fiber 10%, bio-asphalt 10%, nano-graphene modified phenolic resin 10%, silicon carbide whiskers 4%, zirconium boride nanoparticles 3%, graphitized carbon fiber 3%, ginkgo leaf extract antioxidant 2%, cerium oxide 2% and yttrium oxide 1%.

[0074] The method for preparing the carbon / carbon composite material comprises:

[0075] The length of T1000-level high-strength and high-modulus polyacrylonitrile-based carbon fiber is controlled at 3-6 mm, and the selected carbon fiber is pre-stretched. The pre-stretching stress is set to 10% of its breaking strength. The pre-stretching state is maintained for 15 minutes, and the pre-treated high-strength and high-modulus polyacrylonitrile-based carbon fiber is transported to the weaving area through an automatic feeding device. According to the alternating weaving angle of 0° / 90° and the fiber density of about 150 strands / square centimeter, it is woven by a mechanical weaving device under the guidance of a fiber guide device. The weaving speed is controlled at 20 mm / second. During the weaving process, each fiber is tensioned by a tension sensor. Apply constant tension, the tension value is set to 10 grams, the error range is controlled within the weaving angle error of ±1°, the fiber density error is ±5 roots / square centimeter; then carry out the middle layer weaving: when the inner layer weaving reaches 35% of the total thickness of the preform, begin to gradually introduce high thermal conductivity asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber for middle layer weaving, the high thermal conductivity asphalt-based carbon fiber length is 2-5 mm, the nano-silica grafted carbon fiber length is 1-4 mm, the graphitized carbon fiber length is 0.5-2 mm, first, according to the high strength and high modulus polyacrylonitrile-based carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano Silica grafted carbon fiber: graphitized carbon fiber = 7:1:1:1 ratio. The four carbon fibers are mixed and stirred evenly in an automated fiber mixing device at a stirring speed of 100 rpm for 15 minutes. Ultrasonic vibration is also used at a power of 300 watts for 10 minutes. The weaving is carried out according to the requirements of adjusting the weaving angle to ±30° / ±60°. The fiber density gradually decreases to 120 fibers / cm2. During the weaving process, the weaving speed is 15 mm / s. Finally, the outer layer is woven: when the middle layer weaving reaches 60% of the total thickness of the preform, the high-strength and high-modulus polyacrylonitrile is made. Base carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano-silica grafted carbon fiber: graphitized carbon fiber = 5:2:2:1. The fibers are remixed in a new ratio in an automated fiber mixing container. The stirring and ultrasonic treatment parameters are the same as those for the middle layer mixing. The mixed fibers are sent to the outer layer weaving mold through an automated delivery pipeline and weaved at a weaving angle of ±30° / ±60°. The weaving speed is controlled at 12 mm / s. After weaving, the surface impurities and loose fibers are removed by an automated cleaning device, and then automated pre-compaction treatment is carried out. The pre-compaction strength is 1 MPa and the pre-compaction time is 15 minutes.

[0076] The braided preform is placed in a plasma treatment device for plasma treatment. The plasma power of the plasma treatment device is 200 watts, the treatment time is 20 minutes, and the gas is a mixture of oxygen and argon with an oxygen content of 20%.

[0077] A precursor solution containing bio-asphalt and nano-graphene modified phenolic resin is prepared, silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants are added to the precursor solution, and then the mixed solution is subjected to ultrasonic treatment and stirring treatment in sequence, the ultrasonic treatment time is 45 minutes, and the stirring treatment is carried out at 250°C and 1500 rpm for 90 minutes.

[0078] The preform is placed in an impregnation container, the mixed solution is injected and then sealed, supercritical carbon dioxide is charged into the impregnation container, the pressure is set to 12 MPa, the temperature is set to 50°C, and the impregnation treatment time is 3 hours.

[0079] The impregnated preform was placed in a microwave curing device for curing at a power of 750 watts, a time of 15 minutes, and a temperature of 175°C.

[0080] The preform is placed in a chemical vapor deposition reaction chamber for thermal gradient chemical vapor deposition. During the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 75 ml / min, the hydrogen flow rate is 300 ml / min, the center temperature of the thermal gradient is 900°C, the edge temperature is 700°C, and the deposition time is 3.5 hours.

[0081] The preform after chemical vapor deposition is placed in a pressure impregnation device, and the mixed solution is injected into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix. The pressure of the pressure impregnation device is 3.5 MPa, the temperature is 100° C., and the infiltration treatment time is 2 hours.

[0082] The infiltration-treated composite material was placed in a high-temperature heat treatment furnace, argon gas was introduced, and it was heated to 1650°C at a heating rate of 5°C / min, kept warm for 2.5 hours, and then continued to be heated to 2250°C at a heating rate of 3°C / min, kept warm for 3.5 hours. After the treatment, it was cooled to room temperature with the furnace to obtain the final carbon / carbon composite material.

[0083] Embodiment 3

[0084] The carbon / carbon composite materials measured by mass percentage include: the carbon / carbon composite materials measured by mass percentage include: polyacrylonitrile-based carbon fiber 45%, asphalt-based carbon fiber 10%, nano-silica grafted carbon fiber 10%, bio-asphalt 10%, nano-graphene modified phenolic resin 10%, silicon carbide whiskers 4%, zirconium boride nanoparticles 3%, graphitized carbon fiber 3%, ginkgo leaf extract antioxidant 2%, cerium oxide 2% and yttrium oxide 1%.

[0085] The method for preparing the carbon / carbon composite material comprises:

[0086] The length of T1000-level high-strength and high-modulus polyacrylonitrile-based carbon fiber is controlled at 3-6 mm, and the selected carbon fiber is pre-stretched. The pre-stretching stress is set to 10% of its breaking strength. The pre-stretching state is maintained for 15 minutes, and the pre-treated high-strength and high-modulus polyacrylonitrile-based carbon fiber is transported to the weaving area through an automatic feeding device. According to the alternating weaving angle of 0° / 90° and the fiber density of about 150 strands / square centimeter, it is woven by a mechanical weaving device under the guidance of a fiber guide device. The weaving speed is controlled at 20 mm / second. During the weaving process, each fiber is tensioned by a tension sensor. Apply constant tension, the tension value is set to 10 grams, the error range is controlled within the weaving angle error of ±1°, the fiber density error is ±5 roots / square centimeter; then carry out the middle layer weaving: when the inner layer weaving reaches 35% of the total thickness of the preform, begin to gradually introduce high thermal conductivity asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber for middle layer weaving, the high thermal conductivity asphalt-based carbon fiber length is 2-5 mm, the nano-silica grafted carbon fiber length is 1-4 mm, the graphitized carbon fiber length is 0.5-2 mm, first, according to the high strength and high modulus polyacrylonitrile-based carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano Silica grafted carbon fiber: graphitized carbon fiber = 7:1:1:1 ratio. The four carbon fibers are mixed and stirred evenly in an automated fiber mixing device at a stirring speed of 100 rpm for 15 minutes. Ultrasonic vibration is also used at a power of 300 watts for 10 minutes. The weaving is carried out according to the requirements of adjusting the weaving angle to ±30° / ±60°. The fiber density gradually decreases to 120 fibers / cm2. During the weaving process, the weaving speed is 15 mm / s. Finally, the outer layer is woven: when the middle layer weaving reaches 60% of the total thickness of the preform, the high-strength and high-modulus polyacrylonitrile is made. Base carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano-silica grafted carbon fiber: graphitized carbon fiber = 5:2:2:1. The fibers are remixed in a new ratio in an automated fiber mixing container. The stirring and ultrasonic treatment parameters are the same as those for the middle layer mixing. The mixed fibers are sent to the outer layer weaving mold through an automated delivery pipeline and weaved at a weaving angle of ±30° / ±60°. The weaving speed is controlled at 12 mm / s. After weaving, the surface impurities and loose fibers are removed by an automated cleaning device, and then automated pre-compaction treatment is carried out. The pre-compaction strength is 1 MPa and the pre-compaction time is 15 minutes.

[0087] The braided preform is placed in a plasma treatment device for plasma treatment. The plasma power of the plasma treatment device is 300 watts, the treatment time is 30 minutes, and the gas is a mixture of oxygen and argon with an oxygen content of 30%.

[0088] A precursor solution containing bio-asphalt and nano-graphene modified phenolic resin is prepared, silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants are added to the precursor solution, and then the mixed solution is subjected to ultrasonic treatment and stirring treatment in sequence, the ultrasonic treatment time is 60 minutes, and the stirring treatment is carried out at 300°C and 2000 rpm for 120 minutes.

[0089] The preform is placed in an impregnation container, the mixed solution is injected and then sealed, supercritical carbon dioxide is charged into the impregnation container, the pressure is set to 15 MPa, the temperature is set to 60°C, and the impregnation treatment time is 4 hours.

[0090] The impregnated preform was placed in a microwave curing device for curing at a power of 1000 watts, a time of 20 minutes, and a temperature of 200°C.

[0091] The preform is placed in a chemical vapor deposition reaction chamber for thermal gradient chemical vapor deposition. During the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 100 ml / min, the hydrogen flow rate is 400 ml / min, the center temperature of the thermal gradient is 1000°C, the edge temperature is 800°C, and the deposition time is 5 hours.

[0092] The preform after chemical vapor deposition is placed in a pressure impregnation device, and the mixed solution is injected into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix. The pressure of the pressure impregnation device is 5 MPa, the temperature is 120° C., and the infiltration treatment time is 3 hours.

[0093] The infiltration-treated composite material was placed in a high-temperature heat treatment furnace, argon gas was introduced, and the material was heated to 1800°C at a heating rate of 8°C / min, kept warm for 3.5 hours, and then heated to 2500°C at a heating rate of 4°C / min, kept warm for 4.5 hours. After the treatment, the material was cooled to room temperature with the furnace to obtain the final carbon / carbon composite material.

[0094] Embodiment 4

[0095] The carbon / carbon composite materials measured by mass percentage include: the carbon / carbon composite materials measured by mass percentage include: polyacrylonitrile-based carbon fiber 42%, asphalt-based carbon fiber 12%, nano-silica grafted carbon fiber 11%, bio-asphalt 10%, nano-graphene modified phenolic resin 10%, silicon carbide whiskers 4%, zirconium boride nanoparticles 3%, graphitized carbon fiber 3%, ginkgo leaf extract antioxidant 2%, cerium oxide 2% and yttrium oxide 1%.

[0096] The method for preparing the carbon / carbon composite material comprises:

[0097] The length of T1000-level high-strength and high-modulus polyacrylonitrile-based carbon fiber is controlled at 3-6 mm, and the selected carbon fiber is pre-stretched. The pre-stretching stress is set to 10% of its breaking strength. The pre-stretching state is maintained for 15 minutes, and the pre-treated high-strength and high-modulus polyacrylonitrile-based carbon fiber is transported to the weaving area through an automatic feeding device. According to the alternating weaving angle of 0° / 90° and the fiber density of about 150 strands / square centimeter, it is woven by a mechanical weaving device under the guidance of a fiber guide device. The weaving speed is controlled at 20 mm / second. During the weaving process, each fiber is tensioned by a tension sensor. Apply constant tension, the tension value is set to 10 grams, the error range is controlled within the weaving angle error of ±1°, the fiber density error is ±5 roots / square centimeter; then carry out the middle layer weaving: when the inner layer weaving reaches 35% of the total thickness of the preform, begin to gradually introduce high thermal conductivity asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber for middle layer weaving, the high thermal conductivity asphalt-based carbon fiber length is 2-5 mm, the nano-silica grafted carbon fiber length is 1-4 mm, the graphitized carbon fiber length is 0.5-2 mm, first, according to the high strength and high modulus polyacrylonitrile-based carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano Silica grafted carbon fiber: graphitized carbon fiber = 7:1:1:1 ratio. The four carbon fibers are mixed and stirred evenly in an automated fiber mixing device at a stirring speed of 100 rpm for 15 minutes. Ultrasonic vibration is also used at a power of 300 watts for 10 minutes. The weaving is carried out according to the requirements of adjusting the weaving angle to ±30° / ±60°. The fiber density gradually decreases to 120 fibers / cm2. During the weaving process, the weaving speed is 15 mm / s. Finally, the outer layer is woven: when the middle layer weaving reaches 60% of the total thickness of the preform, the high-strength and high-modulus polyacrylonitrile is made. Base carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano-silica grafted carbon fiber: graphitized carbon fiber = 5:2:2:1. The fibers are remixed in a new ratio in an automated fiber mixing container. The stirring and ultrasonic treatment parameters are the same as those for the middle layer mixing. The mixed fibers are sent to the outer layer weaving mold through an automated delivery pipeline and weaved at a weaving angle of ±30° / ±60°. The weaving speed is controlled at 12 mm / s. After weaving, the surface impurities and loose fibers are removed by an automated cleaning device, and then automated pre-compaction treatment is carried out. The pre-compaction strength is 1 MPa and the pre-compaction time is 15 minutes.

[0098] The braided preform is placed in a plasma treatment device for plasma treatment. The plasma power of the plasma treatment device is 100 watts, the treatment time is 10 minutes, and the gas is a mixture of oxygen and argon with an oxygen content of 10%.

[0099] A precursor solution containing bio-asphalt and nano-graphene modified phenolic resin is prepared, silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants are added to the precursor solution, and then the mixed solution is subjected to ultrasonic treatment and stirring treatment in sequence, the ultrasonic treatment time is 30 minutes, and the stirring treatment is carried out at 200°C and 1000 rpm for 60 minutes.

[0100] The preform is placed in an impregnation container, the mixed solution is injected and then sealed, supercritical carbon dioxide is charged into the impregnation container, the pressure is set to 8 MPa, the temperature is 40° C., and the impregnation treatment time is 2 hours.

[0101] The impregnated preform was placed in a microwave curing device for curing at a power of 500 watts, a time of 10 minutes, and a temperature of 150°C.

[0102] The preform is placed in a chemical vapor deposition reaction chamber for thermal gradient chemical vapor deposition. During the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 50 ml / min, the hydrogen flow rate is 200 ml / min, the center temperature of the thermal gradient is 800°C, the edge temperature is 600°C, and the deposition time is 2 hours.

[0103] The preform after chemical vapor deposition is placed in a pressure impregnation device, and the mixed solution is injected into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix. The pressure of the pressure impregnation device is 2 MPa, the temperature is 80°C, and the infiltration treatment time is 1 hour.

[0104] The infiltration-treated composite material was placed in a high-temperature heat treatment furnace, argon gas was introduced, and the material was heated to 1500°C at a heating rate of 3°C / min, kept warm for 1.5 hours, and then heated to 2000°C at a heating rate of 2°C / min, kept warm for 2.5 hours. After the treatment, the material was cooled to room temperature with the furnace to obtain the final carbon / carbon composite material.

[0105] Embodiment 5

[0106] The carbon / carbon composite materials measured by mass percentage include: the carbon / carbon composite materials measured by mass percentage include: polyacrylonitrile-based carbon fiber 42%, asphalt-based carbon fiber 12%, nano-silica grafted carbon fiber 11%, bio-asphalt 10%, nano-graphene modified phenolic resin 10%, silicon carbide whiskers 4%, zirconium boride nanoparticles 3%, graphitized carbon fiber 3%, ginkgo leaf extract antioxidant 2%, cerium oxide 2% and yttrium oxide 1%.

[0107] The method for preparing the carbon / carbon composite material comprises:

[0108] The length of T1000-level high-strength and high-modulus polyacrylonitrile-based carbon fiber is controlled at 3-6 mm, and the selected carbon fiber is pre-stretched. The pre-stretching stress is set to 10% of its breaking strength. The pre-stretching state is maintained for 15 minutes, and the pre-treated high-strength and high-modulus polyacrylonitrile-based carbon fiber is transported to the weaving area through an automatic feeding device. According to the alternating weaving angle of 0° / 90° and the fiber density of about 150 strands / square centimeter, it is woven by a mechanical weaving device under the guidance of a fiber guide device. The weaving speed is controlled at 20 mm / second. During the weaving process, each fiber is tensioned by a tension sensor. Apply constant tension, the tension value is set to 10 grams, the error range is controlled within the weaving angle error of ±1°, the fiber density error is ±5 roots / square centimeter; then carry out the middle layer weaving: when the inner layer weaving reaches 35% of the total thickness of the preform, begin to gradually introduce high thermal conductivity asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber for middle layer weaving, the high thermal conductivity asphalt-based carbon fiber length is 2-5 mm, the nano-silica grafted carbon fiber length is 1-4 mm, the graphitized carbon fiber length is 0.5-2 mm, first, according to the high strength and high modulus polyacrylonitrile-based carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano Silica grafted carbon fiber: graphitized carbon fiber = 7:1:1:1 ratio. The four carbon fibers are mixed and stirred evenly in an automated fiber mixing device at a stirring speed of 100 rpm for 15 minutes. Ultrasonic vibration is also used at a power of 300 watts for 10 minutes. The weaving is carried out according to the requirements of adjusting the weaving angle to ±30° / ±60°. The fiber density gradually decreases to 120 fibers / cm2. During the weaving process, the weaving speed is 15 mm / s. Finally, the outer layer is woven: when the middle layer weaving reaches 60% of the total thickness of the preform, the high-strength and high-modulus polyacrylonitrile is made. Base carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano-silica grafted carbon fiber: graphitized carbon fiber = 5:2:2:1. The fibers are remixed in a new ratio in an automated fiber mixing container. The stirring and ultrasonic treatment parameters are the same as those for the middle layer mixing. The mixed fibers are sent to the outer layer weaving mold through an automated delivery pipeline and weaved at a weaving angle of ±30° / ±60°. The weaving speed is controlled at 12 mm / s. After weaving, the surface impurities and loose fibers are removed by an automated cleaning device, and then automated pre-compaction treatment is carried out. The pre-compaction strength is 1 MPa and the pre-compaction time is 15 minutes.

[0109] The braided preform is placed in a plasma treatment device for plasma treatment. The plasma power of the plasma treatment device is 200 watts, the treatment time is 20 minutes, and the gas is a mixture of oxygen and argon with an oxygen content of 20%.

[0110] A precursor solution containing bio-asphalt and nano-graphene modified phenolic resin is prepared, silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants are added to the precursor solution, and then the mixed solution is subjected to ultrasonic treatment and stirring treatment in sequence, the ultrasonic treatment time is 45 minutes, and the stirring treatment is carried out at 250°C and 1500 rpm for 90 minutes.

[0111] The preform is placed in an impregnation container, the mixed solution is injected and then sealed, supercritical carbon dioxide is charged into the impregnation container, the pressure is set to 12 MPa, the temperature is set to 50°C, and the impregnation treatment time is 3 hours.

[0112] The impregnated preform was placed in a microwave curing device for curing at a power of 750 watts, a time of 15 minutes, and a temperature of 175°C.

[0113] The preform is placed in a chemical vapor deposition reaction chamber for thermal gradient chemical vapor deposition. During the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 75 ml / min, the hydrogen flow rate is 300 ml / min, the center temperature of the thermal gradient is 900°C, the edge temperature is 700°C, and the deposition time is 3.5 hours.

[0114] The preform after chemical vapor deposition is placed in a pressure impregnation device, and the mixed solution is injected into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix. The pressure of the pressure impregnation device is 3.5 MPa, the temperature is 100° C., and the infiltration treatment time is 2 hours.

[0115] The infiltration-treated composite material was placed in a high-temperature heat treatment furnace, argon gas was introduced, and it was heated to 1650°C at a heating rate of 5°C / min, kept warm for 2.5 hours, and then continued to be heated to 2250°C at a heating rate of 3°C / min, kept warm for 3.5 hours. After the treatment, it was cooled to room temperature with the furnace to obtain the final carbon / carbon composite material.

[0116] Embodiment 6

[0117] The carbon / carbon composite materials measured by mass percentage include: the carbon / carbon composite materials measured by mass percentage include: polyacrylonitrile-based carbon fiber 42%, asphalt-based carbon fiber 12%, nano-silica grafted carbon fiber 11%, bio-asphalt 10%, nano-graphene modified phenolic resin 10%, silicon carbide whiskers 4%, zirconium boride nanoparticles 3%, graphitized carbon fiber 3%, ginkgo leaf extract antioxidant 2%, cerium oxide 2% and yttrium oxide 1%.

[0118] The method for preparing the carbon / carbon composite material comprises:

[0119] The length of T1000-level high-strength and high-modulus polyacrylonitrile-based carbon fiber is controlled at 3-6 mm, and the selected carbon fiber is pre-stretched. The pre-stretching stress is set to 10% of its breaking strength. The pre-stretching state is maintained for 15 minutes, and the pre-treated high-strength and high-modulus polyacrylonitrile-based carbon fiber is transported to the weaving area through an automatic feeding device. According to the alternating weaving angle of 0° / 90° and the fiber density of about 150 strands / square centimeter, it is woven by a mechanical weaving device under the guidance of a fiber guide device. The weaving speed is controlled at 20 mm / second. During the weaving process, each fiber is tensioned by a tension sensor. Apply constant tension, the tension value is set to 10 grams, the error range is controlled within the weaving angle error of ±1°, the fiber density error is ±5 roots / square centimeter; then carry out the middle layer weaving: when the inner layer weaving reaches 35% of the total thickness of the preform, begin to gradually introduce high thermal conductivity asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber for middle layer weaving, the high thermal conductivity asphalt-based carbon fiber length is 2-5 mm, the nano-silica grafted carbon fiber length is 1-4 mm, the graphitized carbon fiber length is 0.5-2 mm, first, according to the high strength and high modulus polyacrylonitrile-based carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano Silica grafted carbon fiber: graphitized carbon fiber = 7:1:1:1 ratio. The four carbon fibers are mixed and stirred evenly in an automated fiber mixing device at a stirring speed of 100 rpm for 15 minutes. Ultrasonic vibration is also used at a power of 300 watts for 10 minutes. The weaving is carried out according to the requirements of adjusting the weaving angle to ±30° / ±60°. The fiber density gradually decreases to 120 fibers / cm2. During the weaving process, the weaving speed is 15 mm / s. Finally, the outer layer is woven: when the middle layer weaving reaches 60% of the total thickness of the preform, the high-strength and high-modulus polyacrylonitrile is made. Base carbon fiber: high thermal conductivity asphalt-based carbon fiber: nano-silica grafted carbon fiber: graphitized carbon fiber = 5:2:2:1. The fibers are remixed in a new ratio in an automated fiber mixing container. The stirring and ultrasonic treatment parameters are the same as those for the middle layer mixing. The mixed fibers are sent to the outer layer weaving mold through an automated delivery pipeline and weaved at a weaving angle of ±30° / ±60°. The weaving speed is controlled at 12 mm / s. After weaving, the surface impurities and loose fibers are removed by an automated cleaning device, and then automated pre-compaction treatment is carried out. The pre-compaction strength is 1 MPa and the pre-compaction time is 15 minutes.

[0120] The braided preform is placed in a plasma treatment device for plasma treatment. The plasma power of the plasma treatment device is 300 watts, the treatment time is 30 minutes, and the gas is a mixture of oxygen and argon with an oxygen content of 30%.

[0121] A precursor solution containing bio-asphalt and nano-graphene modified phenolic resin is prepared, silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants are added to the precursor solution, and then the mixed solution is subjected to ultrasonic treatment and stirring treatment in sequence, the ultrasonic treatment time is 60 minutes, and the stirring treatment is carried out at 300°C and 2000 rpm for 120 minutes.

[0122] The preform is placed in an impregnation container, the mixed solution is injected and then sealed, supercritical carbon dioxide is charged into the impregnation container, the pressure is set to 15 MPa, the temperature is set to 60°C, and the impregnation treatment time is 4 hours.

[0123] The impregnated preform was placed in a microwave curing device for curing at a power of 1000 watts, a time of 20 minutes, and a temperature of 200°C.

[0124] The preform is placed in a chemical vapor deposition reaction chamber for thermal gradient chemical vapor deposition. During the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 100 ml / min, the hydrogen flow rate is 400 ml / min, the center temperature of the thermal gradient is 1000°C, the edge temperature is 800°C, and the deposition time is 5 hours.

[0125] The preform after chemical vapor deposition is placed in a pressure impregnation device, and the mixed solution is injected into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix. The pressure of the pressure impregnation device is 5 MPa, the temperature is 120° C., and the infiltration treatment time is 3 hours.

[0126] The infiltration-treated composite material was placed in a high-temperature heat treatment furnace, argon gas was introduced, and the material was heated to 1800°C at a heating rate of 8°C / min, kept warm for 3.5 hours, and then heated to 2500°C at a heating rate of 4°C / min, kept warm for 4.5 hours. After the treatment, the material was cooled to room temperature with the furnace to obtain the final carbon / carbon composite material.

[0127] Comparative Example 1

[0128] The carbon / carbon composite material includes, by weight percentage, 40% polyacrylonitrile-based carbon fiber, 15% viscose-based carbon fiber, 10% asphalt-based carbon fiber, 20% phenolic resin, 10% furan resin, 3% silicon carbide particles and 2% potassium titanate whiskers.

[0129] The method for preparing the carbon / carbon composite material comprises:

[0130] Polyacrylonitrile-based carbon fiber with a length of 3-6 mm, viscose-based carbon fiber with a length of 2-5 mm, and asphalt-based carbon fiber with a length of 4-7 mm were selected respectively, and the three carbon fibers were first mixed in a three-dimensional mixer for 45 minutes to ensure uniform mixing. Then the mixed carbon fiber was placed in a preform mold, and a multi-directional weaving process was adopted. The weaving angles were 0° / 90° and ±45° combinations, and the fiber density was controlled at 110 fibers / square centimeter. After weaving, hot pressing was performed under a pressure of 0.5 MPa, the temperature was set to 165°C, and the time was 25 minutes to obtain a carbon fiber preform.

[0131] After mixing phenolic resin and furan resin in proportion, add an appropriate amount of acetone and stir to dissolve to prepare an impregnation solution with a solid content of about 55%. Put the preform into the impregnation solution and impregnate it for 2 hours under a vacuum environment with an impregnation pressure of -0.07 MPa. Then take it out and cure it in an oven at 100°C for 4 hours. Put the cured preform into a carbonization furnace and heat it to 900°C at a heating rate of 4°C / min under nitrogen protection. The carbonization time is 2 hours. Repeat the impregnation-curing-carbonization process 5 times.

[0132] Using acetylene as the gas source and hydrogen as the carrier gas, the acetylene flow rate is controlled at 50 ml / min and the hydrogen flow rate is 150 ml / min. The preform that has undergone multiple impregnation-curing-carbonization is placed in the chemical vapor deposition reaction chamber, and the deposition temperature is set to 1100°C, the deposition pressure is set to 8 kPa, and the deposition time is set to 2 hours.

[0133] The prepared composite material was placed in a high-temperature heat treatment furnace, argon gas was introduced, and the material was heated to 1900° C. at a heating rate of 7° C. / min, kept at that temperature for 2.5 hours, and cooled to obtain a carbon / carbon composite material.

[0134] Comparative Example 2

[0135] The carbon / carbon composite material includes, by weight percentage, 30% high-strength polyacrylonitrile-based carbon fiber, 20% high-modulus polyacrylonitrile-based carbon fiber, 10% graphite fiber, 25% coal tar pitch, 10% modified phenolic resin, 2% boron oxide and 3% titanium diboride.

[0136] The method for preparing the carbon / carbon composite material comprises:

[0137] The length of high-strength polyacrylonitrile-based carbon fiber is 4-7 mm, the length of high modulus polyacrylonitrile-based carbon fiber is 3-6 mm, and the length of graphite fiber is 2-5 mm. The three carbon fibers are mixed in a high-speed mixer for 55 minutes. A small amount of dispersant is added during mixing to prevent fiber agglomeration. Then, a preform is prepared by a needle punching process. First, a layer of fiber mesh is laid, and then needle-punched by a needle punching machine with a needle-punching density of 250 needles / square centimeter. The laying and needle-punching process is repeated for 6 layers, and finally a preform with a certain thickness and strength is obtained, with a fiber density of about 125 needles / square centimeter.

[0138] After the coal tar is heated to 220°C and melted, it is evenly mixed with the modified phenolic resin to obtain a matrix precursor mixture. The preform is immersed in the precursor mixture for 50 minutes at a temperature of 210°C. After immersion, it is taken out and pyrolyzed in a vacuum environment at a pyrolysis temperature of 800°C, a pyrolysis pressure of -0.04 MPa, and a pyrolysis time of 2 hours. The immersion-pyrolysis process is repeated 4 times.

[0139] Using ethylene as the gas source and argon as the diluent gas, the ethylene flow rate is 40 ml / min, the argon flow rate is 110 ml / min, the preform after impregnation-pyrolysis treatment is placed in the chemical vapor infiltration reaction chamber, the reaction temperature is set to 900°C, the reaction pressure is 4 kPa, and the infiltration time is 3 hours.

[0140] The composite material was placed in a high-temperature furnace, argon gas was introduced, and the temperature was increased to 2100° C. at a heating rate of 5° C. / min and kept at this temperature for 3 hours.

[0141] The properties of the carbon / carbon composite materials obtained in the above examples 1 to 6 and comparative examples 1 and 2 were measured respectively, and the comparison table obtained is as follows:

[0142]

[0143] By comparison, the embodiments use a variety of carbon fibers with special functions, such as polyacrylonitrile-based carbon fibers to provide a higher strength foundation, asphalt-based carbon fibers to help heat conduction, nano-silica grafted carbon fibers to enhance interfacial bonding, and graphitized carbon fibers to improve self-lubrication and conductivity, etc., and each carbon fiber is gradiently distributed in different layers according to a certain proportion. The synergistic effect of these multiple types of carbon fibers enables the material to effectively disperse stress under different force modes (tensile, compression, bending, shear). In contrast, the simple mixture of conventional polyacrylonitrile-based, viscose-based and asphalt-based carbon fibers used in Comparative Example 1, and the combination of high-strength, high-modulus polyacrylonitrile-based and graphite fibers in Comparative Example 2 are poor in fiber functional diversity and synergy, resulting in their tensile, compression, bending and shear strengths being significantly lower than those in the embodiments. For example, the tensile strength in the embodiments is generally above 800-900MPa, while that in Comparative Example 1 is only about 650-700MPa. The embodiment uses bio-asphalt and nano-graphene modified phenolic resin as matrix precursors, and adds silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide, yttrium oxide and natural plant extract antioxidants. The combination of bio-asphalt and modified phenolic resin can form a more stable and high-quality carbon matrix during the carbonization process, improving the overall structural stability of the material. Silicon carbide whiskers and zirconium boride nanoparticles enhance the hardness and wear resistance of the material and have a positive contribution to compression and shear strength; cerium oxide and yttrium oxide together with antioxidants significantly improve the antioxidant performance. Comparative Example 1 uses ordinary phenolic resin and furan resin as matrix precursors. The additives are only silicon carbide particles and potassium titanate whiskers, which have limited strengthening and anti-oxidation effects on the matrix. The matrix precursors of Comparative Example 2 are coal tar and modified phenolic resin, and the additives boron oxide and titanium diboride mainly focus on improving anti-oxidation and high-temperature performance, but are not as good as the embodiment in terms of overall performance synergy. This makes the embodiment excellent in high temperature resistance and oxidation resistance. For example, the high temperature resistance of the embodiment can generally reach above 2000°C, and the oxidation resistance (oxidation weight loss rate) can be controlled at about 3% or even lower under the condition of 1500°C / 10h, while the high temperature resistance of Comparative Example 1 is only about 1600°C, and the oxidation weight loss rate is as high as more than 7%.

[0144] The preform weaving of the embodiment adopts a carefully designed gradient structure and precise weaving parameter control. First, the inner layer is mainly high-strength and high-modulus polyacrylonitrile-based carbon fiber, the weaving angle is 0° / 90° alternating, and the fiber density is high. Then, when transitioning to the outer layer, the fiber type and weaving angle are adjusted to reduce the fiber density, forming a preform structure with gradual mechanical and thermal properties. This weaving method enables the material to better adapt to the stress and heat transfer requirements at different parts, effectively improving the comprehensive performance of the material. The multi-directional weaving process of Example 1 and the needle punching process of Example 2 are relatively simple, lacking this gradient structure design for performance optimization, resulting in the internal of the material The stress distribution is not reasonable enough, which affects the mechanical properties. In the embodiment, the woven preform is subjected to plasma treatment, and the surface of the carbon fiber is etched and activated by using plasma power, treatment time and a specific oxygen-argon mixed gas, thereby enhancing the bonding force between the carbon fiber and the subsequent matrix precursor. This step is not adopted in the comparative example, so that the interface bonding is relatively weak, and interface separation is prone to occur when subjected to force, which affects the overall strength of the material, especially the tensile and bending strength. The embodiment adopts supercritical carbon dioxide to assist impregnation, so that the precursor solution can more fully penetrate into the pores of the preform, and combined with microwave curing, rapid and uniform curing is achieved. The porosity is reduced, the density and uniformity of the matrix are improved, thereby improving the strength and stability of the material. Comparative Example 1 adopts conventional vacuum impregnation and oven curing, and Comparative Example 2 adopts an impregnation-pyrolysis process, which is not as good as the embodiment in terms of impregnation effect and curing uniformity, resulting in limited mechanical properties and high temperature resistance. The thermal gradient chemical vapor deposition combined with the pressure impregnation infiltration process in the embodiment controls parameters such as gas source flow, temperature gradient and pressure to make carbon grow directionally on the surface and pores of the preform and combine with the impregnated matrix, further densifying the carbon matrix, optimizing the microstructure of the material, and improving the mechanical properties and high temperature resistance Temperature performance, the chemical vapor deposition or chemical vapor infiltration process parameter settings of Examples 1 and 2 are relatively simple, without this multi-step coordinated optimization process design, the effect of improving material performance is not obvious, the embodiment adopts a two-stage high-temperature heat treatment, first a preliminary graphitization treatment at 1500-1800°C, and then a deep graphitization treatment at 2000-2500°C, so that the carbon matrix structure is gradually improved, the crystal structure is more regular, and the mechanical, thermal and conductive properties of the material are comprehensively improved. The high-temperature heat treatment process of the comparative example is relatively simple, without such fine temperature control and multi-stage treatment, the performance improvement of the material is limited.

[0145] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.

[0146] Each embodiment of the present invention is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0147] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0148] While the disclosure has been described in conjunction with specific embodiments thereof, many alternatives, modifications and variations of these embodiments will be apparent to those skilled in the art in light of the foregoing description.

[0149] One or more embodiments of the present invention are intended to cover all such replacements, modifications and variations that fall within the scope of protection of the present invention. Therefore, any omissions, modifications, equivalent replacements, improvements, etc. made within the spirit and principles of one or more embodiments of the present invention should be included in the scope of protection of this disclosure.

Claims

1. A method for preparing a carbon / carbon composite material, characterized in that: The raw materials of the carbon / carbon composite material include, by weight percentage, 40%-55% polyacrylonitrile-based carbon fiber, 10%-25% asphalt-based carbon fiber, 8%-20% nano-silicon dioxide grafted carbon fiber, 8%-20% bio-asphalt, 8%-15% nano-graphene modified phenolic resin, 3%-6% silicon carbide whisker, 2%-4% boride nanoparticles, 2%-4% graphitized carbon fiber, 1%-3% natural plant extract antioxidant, 2%-4% cerium oxide nanoparticles, and 1%-2% yttrium oxide nanoparticles. The preparation method comprises: S1: polyacrylonitrile-based carbon fiber, asphalt-based carbon fiber, nano-silica grafted carbon fiber and graphitized carbon fiber are multi-layered woven according to an inside-outside gradient structure to obtain a preform; S2: placing the braided preform in a plasma treatment device for plasma treatment; S3: preparing a precursor solution containing bio-asphalt and nano-graphene modified phenolic resin, adding silicon carbide whiskers, zirconium boride nanoparticles, cerium oxide nanoparticles, yttrium oxide nanoparticles and natural plant extract antioxidants to the precursor solution, and then sequentially or simultaneously subjecting the mixed solution to ultrasonic treatment and stirring treatment; S4: placing the preform into an impregnation container, injecting the mixed solution and sealing the container, and filling the impregnation container with supercritical carbon dioxide; S5: placing the impregnated preform into a microwave curing device for curing; S6: placing the preform in a chemical vapor deposition reaction chamber to perform thermal gradient chemical vapor deposition; S7: placing the preform after chemical vapor deposition in a pressure impregnation device, injecting the mixed solution into the pressure impregnation device to perform infiltration treatment on the preform to densify the carbon matrix; S8: placing the composite material that has undergone the infiltration treatment into a high-temperature heat treatment furnace for high-temperature heat treatment.

2. The method for preparing a carbon / carbon composite material according to claim 1, characterized in that: In step S2, the plasma power of the plasma treatment equipment is 100-300 watts, the treatment time is 10-30 minutes, and the gas is a mixture of oxygen and argon with an oxygen content of 10%-30%.

3. The method for preparing a carbon / carbon composite material according to claim 1, characterized in that: In step S3, the ultrasonic treatment is performed for 30-60 minutes, and the stirring treatment is performed at 200-300°C and 1000-2000 rpm for 60-120 minutes.

4. The method for preparing a carbon / carbon composite material according to claim 1, characterized in that: In step S4, supercritical carbon dioxide is charged to a set pressure of 8-15 MPa, a temperature of 40-60° C., and an immersion treatment time of 2-4 hours; In step S5, the curing treatment is performed at a power of 500-1000 watts, a time of 10-20 minutes, and a temperature of 150-200°C.

5. The method for preparing a carbon / carbon composite material according to claim 1, characterized in that: In step S6, during the thermal gradient chemical vapor deposition process on the preform, methane and hydrogen are used as gas sources, the methane flow rate is 50-100 ml / min, the hydrogen flow rate is 200-400 ml / min, the center temperature of the thermal gradient is 800-1000° C., the edge temperature is 600-800° C., and the deposition time is 2-5 hours; In step S7, the pressure of the pressure impregnation equipment is 2-5 MPa, the temperature is 80-120°C, and the infiltration treatment time is 1-3 hours.

6. The method for preparing a carbon / carbon composite material according to claim 1, characterized in that: Step S8 specifically includes: S81: placing the composite material into a high temperature heat treatment furnace, introducing argon gas, heating to 1500-1800° C. at a heating rate of 3-8° C. / min, and keeping the temperature for 1.5-3.5 hours; S82: Continue heating the temperature to 2000-2500° C. at a heating rate of 2-4° C. / min, and keep the temperature for 2.5-4.5 hours.

7. The method for preparing a carbon / carbon composite material according to claim 1, characterized in that: The raw materials of the carbon / carbon composite material include, by weight percentage, 42%-47% polyacrylonitrile-based carbon fiber, 10%-16% asphalt-based carbon fiber, 10%-16% nano-silicon dioxide grafted carbon fiber, 10% bio-asphalt, 10% nano-graphene modified phenolic resin, 4% silicon carbide whisker, 3% boride nanoparticles, 3% graphitized carbon fiber, 2% natural plant extract antioxidant, 2%-4% cerium oxide nanoparticles and 1%-2% yttrium oxide nanoparticles.

Citation Information

Patent Citations

  • SiC-ZrC-ZrB2 nano complex phase ceramic modified C / C composite material and preparation method thereof

    CN104230367A

  • Rapid preparation method of low-cost carbon / carbon composite material

    CN105924199A